Electric field control of resistive switching and magnetization in epitaxial LaBaCo2O5+δ thin films - Shaibo, Jamal; Yang, Rui; Wang, Zhe; He-Ming, Huang; Xiong, Jue; Guo, Xin (Physical chemistry chemical physics : PCCP, 2019)
The low operating temperature and volatile characteristics of the magnetization change are the main obstacles for the practical applications of spintronic and magnetic memories. In this work, both the resistive switching and magnetization switching are realized in Pt/LaBaCo2O5+δ (LBCO)/Nb-doped SrTiO3 (Nb-STO) devices at room temperature through an electric field. Unlike the traditional approach of an external stress inducing a volatile magnetization change, the magnetization in the Pt/LBCO/Nb-STO device is modulated by an electrical field, along with the resistive switching. The resistive and magnetization switching can be attributed to the variation of the depletion layer width at the LBCO/Nb-STO interface via oxygen vacancy migration and the increase/decrease of the Co–O–Co bond length, respectively. The present device with the synchronous manipulation of both resistance and magnetization at room temperature can be applied in nonvolatile resistive memories and novel magnetic multifunctional devices.